2022
DOI: 10.1002/aenm.202200615
|View full text |Cite
|
Sign up to set email alerts
|

High‐Energy Ni‐Rich Cathode Materials for Long‐Range and Long‐Life Electric Vehicles

Abstract: of the global EV market, Li-ion battery (LIB) technology has progressed to meet the demand for longer driving ranges and extended service lives, while increasing the thermal stability and reducing the cost of the battery. As the performance of LIBs is largely determined by the cathode material, the development of high-performance LIBs for EVs has focused on increasing the capacity of the cathode by usingHowever, cathodes with a high Ni content suffer from inherent structural and chemical instabilities, which l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…Trends of R sf and R ct manifested the less structural deterioration and surface side reaction during the electrochemical process. 37,39 Overall, the Al introduction and CeO 2− x coating reinforced the crystal structure and interfacial stability, hindering the irreversible phase transitions and surface evolution during cycling.…”
Section: Resultsmentioning
confidence: 99%
“…Trends of R sf and R ct manifested the less structural deterioration and surface side reaction during the electrochemical process. 37,39 Overall, the Al introduction and CeO 2− x coating reinforced the crystal structure and interfacial stability, hindering the irreversible phase transitions and surface evolution during cycling.…”
Section: Resultsmentioning
confidence: 99%
“…The CSG-NCMA90 cathode displayed a capacity retention of 90.6% and 94.1% aer 1000 cycles at 100% and over 60% depths of discharge, respectively. Namkoong et al 125 introduced 1 mol% B into Li [Ni0 .88 Co 0.10 Al 0.02 ]O 2 CSG (CSG-NCAB87) and studied the effect of exposure time to the electrolyte on the cathode material at a high state of charge (SOC). The result showed that the capacity decay increased with the increase of exposure time.…”
Section: Nrlos With a Radially Elongated Structurementioning
confidence: 99%
“…The additional modification that regulates the chemical–mechanical properties of the single-crystalline Ni-rich cathode is necessary to be conducted for enhancing the electrochemical performance of LIBs, such as cation/anion doping and surface coating. , Ionic doping (such as B, F, Mg, Mo, and Nb) can stabilize the internal lattice structure by forming a stable crystal network structure, which effectively suppresses the structure collapse caused by the anisotropic lattice strain during H2–H3 phase transition . Meanwhile, the conductivity of cathode electrons/ions is also enhanced by the introduction of additional elements into the internal lattice structure, beneficial to promoting lithium-ion diffusion.…”
Section: Introductionmentioning
confidence: 99%